The Effect of Competence, Motivation, Work Environment and Work Facilities on The Expenditure Treasurer Performance - Mohamad Fajar Budiman; Akadun Akadun; Milwan Milwan (LPPM Universitas Terbuka, 2022)
Purpose – This study aims to determine and analyze the effect of competence, motivation, as well as work environment and facilities on the performance of the expenditure treasurer at the APBN management unit in North Kalimantan Province. Methodology – The participants were 213 expenditure treasurers which were selected by the simple random sampling technique. Furthermore, the number of samples was determined by using the Yamane formula and a total of 139 respondents were obtained. The data collection technique used questionnaires, namely the Guttman, Likert, and Rating Scales. In addition, the data were analyzed using multiple linear regression with the aid of SPSS For Windows. Findings – The results showed competence, motivation, as well as work environment and facilities had a positive and significant effect on the performance of the expenditure treasurer. Therefore, each of the work units managing the State Budget in North Kalimantan Province needs to pay more attention to the factors that affect performance. Originality – This study provides a new perspective on the effect of competence, motivation, as well as work environment and facilities on expenditure treasurer performance, which has never been carried out in previous literature.